Implementasi Otonomi dalam Praktik Kedokteran di Indonesia: Tinjauan Etik dan Hukum: The Principle of Autonomy in Medical Practice in Indonesia: A Review of Ethics and Laws - Arthanti, Widyana Beta (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
The principle of autonomy is one of the main pillars of medical bioethics, realized through the process of obtaining informed consent for medical procedures. In Indonesia, the implementation of informed consent has not yet fully reflected respect for patients’ autonomous rights. The process of obtaining medical consent is often perceived merely as an administrative formality rather than a meaningful two-way communication between doctor and patient. This article aims to examine the principle of autonomy in Indonesian medical practice from both ethical and legal perspectives. The study employs a normative legal research method using a statute approach and conceptual approach, supported by primary, secondary, and tertiary legal materials relevant to the period between 2015 and 2025. The findings indicate that the main obstacles in implementing informed consent include the persistence of a paternalistic culture, low patient health literacy, limited consultation time, and the use of overly technical consent forms that hinder understanding. Although relevant regulations already exist, their practical application remains suboptimal. A comprehensive strategy involving clinical communication training, patient empowerment, and periodic ethical audits is needed to ensure full protection of patient rights.